Whole-plant forage and grain sorghum silages for growing cattle - B. Kirch; S. Hamma; K. Bolsen; H. Ilg; J. Hoover (Kansas Agricultural Experiment Station Research Reports, 1987)
Four trials were conducted to determine the feeding value of whole-plant forage and grain sorghum silages. In general, growing cattle fed grain sorghum hybrids (NK2778, Funk's 550, DeKalb 42Y, DeKalb E67) out performed those fed forage sorghum silages. Only moderate to high grain-content, forage sorghums (Buffalo Canex, Pioneer 947, Acco 351) gave performances that approached the grain sorghums. Low grain-content and nonheading forage sorghums (DeKalb 25E, Funk's G-1990) resulted in the poorest cattle performance. These studies indicate that grain content of a sorghum silage is the major determinant of cattle performance and that whole-plant grain sorghums should produce the fastest and most efficient gains in growing programs.
Keywords: Cattlemen' s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Forage; Grain sorghum silage